MENATA PANGKALAN ANGKATAN LAUT GUNA MEMPERKUAT KEDAULATAN MARITIM INDONESIA - Darma Agung S.I; Hollanda Arief K (Jurusan Ilmu Hubungan Internasional, 2017)
Fostering maritime sovereignty not only focusing on strengthening fire power through main weapons system acquisition, but also the supports factor of a marine operation, such as naval bases, is also worth noting. Naval base play an important role in supporting the operation of the Navy. The development and deployment of TNI forces, including naval bases, should pay attention to and prioritize security-prone areas, border areas, conflict-prone areas and remote islands in accordance with geographical and defense strategies. By relocating the main naval base near to the operating area, or vulnerable to threat areas, it can reduce response time, saving operational costs, increase operational reach, minimize potential threats, and become alternative solutions to budget constraints. Using Central Feature method on ArcGIS, based on threat perception, we locate several new position of naval base.